THE EFFECT OF LIQUIDITY, MANAGERIAL OWNERSHIP AND LEVERAGE ON THE VALUE OF COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2016-2020 - Martha, Lidya; Rina, Kastu (Jurnal Apresiasi Ekonomi, 2023)
ABSTRACTThe purpose of this study is to determine the effect of financial performance, managerial ownership and leverage on firm value. The variables in this study are Liquidity, Managerial Ownership and Leverage. Sampling using purposive sampling technique with certain criteria. Which resulted in a sample of 24 companies listed on the Indonesia Stock Exchange in 2016-2020. The analysis in this study uses panel data regression analysis with the results that Liquidity has a positive and significant effect on firm value and Managerial Ownership has a negative and insignificant effect on firm value, while Leverage has an effect on firm value. The results of the study show that firm value (Tobins'q) is influenced by the Cash Ratio (CR). The results of the second hypothesis, namely the t test (partial test) shows the value of the t-statistic CR 2.712511 with a probability value of 0.0078, then H0 is rejected. The results of the study show that firm value (Tobins'q) is negatively and insignificantly affected by Managerial Ownership. This is evidenced by the results of the t test (partial test) which shows the t-statistic value of KM -1.012049 with a probability value of 0.3138, then H0 is accepted. The results of the study show that the value of the company (Tobins'q) is positively and significantly affected by the Debt to Equity Ratio (DER). This is evidenced by the results of the t test (partial test) which shows the t-statistic value of DER 8.649084 with a probability value of 0.0000, then H0 is rejected.Keywords: likuidity, managerial ownership, leverage, firm value